Attenuation of Autoimmune Phenomena in a Patient with Autoimmune Polyglandular Syndrome Type 1 - Jill D. Jacobson; Julia R. Broussard; Courtney Marsh; Brandon Newell (Case Reports in Endocrinology)
Autoimmune polyglandular syndrome type 1 (APS1) is a progressive life-threatening illness with no known cure. Current treatments involve replacement of the hormone deficiencies that result from autoimmune destruction of multiple endocrine organs. We report on a girl whose disease was progressing rapidly until she began on immunosuppressive agents. A healthy 6-year-old girl with no remarkable medical history presented with new onset hypocalcemic seizures and primary hypoparathyroidism. Howell-Jolly bodies consistent with autoimmune hyposplenism were also noted. Genetic testing revealed compound heterozygosity for 2 disease-associated variants in the autoimmune regulator (AIRE) gene. She later developed elevated liver enzymes, primary adrenal insufficiency, and alopecia totalis. Serologic testing revealed antibodies to 21-hydroxylase, intrinsic factor, and smooth muscle. Hydrocortisone was initiated for adrenal insufficiency. Shortly afterwards, her liver enzymes normalized, and her smooth muscle antibody levels began to decline. Serologic testing performed at age 11 revealed seropositivity for glutamic acid decarboxylase (GAD) antibodies, antinuclear antibodies, and Sjögren syndrome A (SSA) antibodies. At age 12, she was given 2 doses of rituximab. Hair loss rapidly progressed to alopecia totalis and then to alopecia universalis, at which time oral methotrexate treatment was initiated. For the past 7 years while on glucocorticoid and methotrexate treatment, our patient has displayed normalization of 2 antibodies, a lack of progression to additional autoimmune diseases, and experienced reversal of alopecia universalis.